Plate-like Buckling Resistance of Longitudinally Stiffened Plates Subjected to Pure Compression - Kövesdi, Balázs (Periodica Polytechnica Civil Engineering, 2019)
Plate buckling resistance calculation of orthotropic plates and the determination of the effective width is highly important in the design of bridges. The current effective width calculation method provided by the EN 1993-1-5 [1] is developed for I-sections subjected to bending. Previous research results proved that the application of the plate buckling curve can overestimate the buckling resistance in case of square box sections subjected to pure compression. It means, that the required safety level of the Eurocode is not fulfilled for buckling resistance of plates in compression. Several previous studies proved the unconservatism of the EN 1993-1-5 for this special case, where the plate has no support coming from the adjacent plates. The question arises, if the above mentioned calculation process also leads to unsafe resistances for other structural details, or this is the specialty of the analyzed worst case scenario. Longitudinally stiffened plates (bottom flange of steel box sections) subjected to pure compression could be also a worst case scenario, because they are not supported by adjacent plates and they are loaded by pure compression. Therefore, the current research focuses on the investigation of longitudinally stiffened orthotropic plates loaded by pure compression and investigates (1) the plate-like buckling resistance, (2) the applicability of the Winter curve and (3) determines the necessary partial safety factor according to the safety requirements of the Eurocode. In the present paper the results of an extensive numerical research program are introduced and the applicability of the Winter curve is evaluated based on the safety requirements of the Eurocode.